Making fundamental scientific discoveries by combining information from literature, databases, and computational tools – An example - Stielow, Bastian; Simon, Clara; Liefke, Robert (Computational and structural biotechnology journal, 2021)
In recent years, the amount of available literature, data and computational tools has increased exponentially, providing opportunities and challenges to make use of this vast amount of material. Here, we describe how we utilized publicly available information to identify the previously hardly characterized protein SAMD1 (SAM domain-containing protein 1) as a novel unmethylated CpG island-binding protein. This discovery is an example, how the richness of material and tools on the internet can be used to make scientific breakthroughs, but also the hurdles that may occur. Specifically, we discuss how the misrepresentation of SAMD1 in literature and databases may have prevented an earlier characterization of this protein and we address what can be learned from this example.